Web-Based 360 Degree Virtual Tour Video for Promoting Cultural Tourism at Pura Puseh and Pura Desa Batuan - Gede Wirya; Putu Gede Maha Vivaldi Pradnyana (LPPM Universitas Bhinneka Nusantara, 2026)
Pura Puseh and Pura Desa Batuan in Gianyar Regency are prestigious National Cultural Heritage sites characterized by ancient Balinese architecture and deep historical roots dating back to 1020 AD. Despite their significance, a reliance on conventional promotional media has resulted in a lack of immersive experiences for tourists, often causing the site to be overlooked as a mere transit point. This study addresses this gap by designing and developing an immersive, web-based Virtual Tour 360 Video platform using the systematic ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The production utilized 360-degree 4K panoramic videos, edited with Adobe Premiere and 3DVista, integrating hotspot navigation and AI-animated characters to enhance storytelling. Technical validation via Black Box Testing on 6 functional test cases (BB-01 to BB-06) resulted in a 100%